What happens when we die? - Nystrom, Carolyn; Hanna, Wayne A. (Chicago : Moody Press, 1981)
Presents a brief description of death, heaven, and Christ's death and resurrection.
Keywords: Death -- Religious aspects -- Christianity -- Juvenile literature; Heaven -- Christianity -- Juvenile literature; Death; Heaven